2022
DOI: 10.1108/er-03-2021-0090
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 challenges and employees' stress: mediating role of family-life disturbance and work-life imbalance

Abstract: PurposeThe paper focuses on examining the relationship between challenges caused by COVID-19 pandemic and employees' stress through the mediating role of family-life disturbance and work-life imbalance.Design/methodology/approachA total of 1,556 respondents from 45 countries across all continents were included in this survey. Statistical techniques such as exploratory factor analysis (EFA), confirmatory factor analysis (CFA), correlations, multiple regression and bootstrapping were used to analyse the data.Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…Second, overtime, support from leaders and colleagues and managing work–life balance are positively related to job engagement. In their recent study on the impact of COVID-19, Kundu et al. (2022) found that managing work–life balance is an important mediator to stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, overtime, support from leaders and colleagues and managing work–life balance are positively related to job engagement. In their recent study on the impact of COVID-19, Kundu et al. (2022) found that managing work–life balance is an important mediator to stress.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show how working from home during the pandemic induced stress and provided challenges to the well-being and work-life balance of employees exposed to these arrangements (e.g. Galanti et al, 2021;Kundu et al, 2022;Ingusci et al, 2021). Researchers have also uncovered strategies to meet these challenges, such as providing access to job crafting to relieve stress (Ingusci et al, 2021) and using boundary work-life tactics (Rapp et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant implications for management practice are also highlighted, elucidating the role of the first-line supervisors in fostering the P.O-fit dimensions, controlling MHIW and retaining WP growth during COVID-19. This study also extends the ongoing scholarly discourse of the COVID-19 pandemic (Adekoya et al ., 2022; Amankwah-Amoah, 2022; Amankwah-Amoah and Hinson, 2022; Gashi et al ., 2022; Rozman and Tominc, 2022; Rožman and Čančer, 2022; Kundu et al. , 2022) by integrating and incorporating insights on mental health at the workplace to enrich the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…The European Foundation for the Improvement of Living and Working Conditions 20 reports fatigue to be especially high among women with young children who worked from home. Kundu et al 21 reported that COVID-19 challenges were associated with stress, mediated by family-life disturbances and work-life imbalance. Meyer et al 22 report an increase in exhaustion among women, which was augmented if the women cared for children, had low autonomy, and low partner support.…”
mentioning
confidence: 99%